2013
DOI: 10.1088/0004-6256/145/2/51
|View full text |Cite
|
Sign up to set email alerts
|

Gnosis: The First Instrument to Use Fiber Bragg Gratings for Oh Suppression

Abstract: The near-infrared is an important part of the spectrum in astronomy, especially in cosmology because the light from objects in the early universe is redshifted to these wavelengths. However, deep near-infrared observations are extremely difficult to make from ground-based telescopes due to the bright background from the atmosphere. Nearly all of this background comes from the bright and narrow emission lines of atmospheric hydroxyl (OH) molecules. The atmospheric background cannot be easily removed from data b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…Furthermore, because the star light is carried in single-mode optical fibres, other photonic technologies can be applied, such as fibre Bragg gratings for narrow-band spectral filtering of detrimental background light. This has been successfully applied to suppress 148 bright emission lines arising from hydroxyl groups in our Earth's atmosphere [118]. However, fibrebased photonic lanterns are difficult to scale to higher number of single-mode fibres and are labour intensive to fabricate.…”
Section: Integrated Photonic Lanternsmentioning
confidence: 99%
“…Furthermore, because the star light is carried in single-mode optical fibres, other photonic technologies can be applied, such as fibre Bragg gratings for narrow-band spectral filtering of detrimental background light. This has been successfully applied to suppress 148 bright emission lines arising from hydroxyl groups in our Earth's atmosphere [118]. However, fibrebased photonic lanterns are difficult to scale to higher number of single-mode fibres and are labour intensive to fabricate.…”
Section: Integrated Photonic Lanternsmentioning
confidence: 99%
“…Observations with GNOSIS 6,8 showed that although strong OH suppression was achieved by the FBGs, the overall sensitivity of IRIS2 was not improved. This was due to two reasons: the low overall throughput of GNOSIS + IRIS2 meant that below 1.6 µm the background was dominated by the detector dark current, and above this the background was dominated by thermal emission from the warm relay optics.…”
Section: Thermal Backgroundmentioning
confidence: 97%
“…Thus, a perfect lantern device has an intrinsically limited bandwidth, since the number of modes could only be perfectly matched over a restricted wavelength ranges determined by the modal cut-off of the multimode waveguide at those wavelengths and the number of single-mode waveguides. Devices with a 300 nm bandwidth have been already demonstrated with a minimum 85% transmission at the edges of the usable wavelength span [13,22].…”
Section: Wavelength Dependencementioning
confidence: 99%
“…An OH-sky suppression instrument called GNOSIS [22], installed at the 3.9 m Anglo Australian Telescope (AAT) in Australia ( Figure 5A), was made possible by photonic lantern technology. This instrument efficiently transfers the light captured and coupled into multimode fibers by the telescope into single-mode fibers through a photonic lantern.…”
Section: Astronomy and Spectroscopymentioning
confidence: 99%